2016
DOI: 10.5812/aapm.31880
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Corrective Surgery of Congenital Diaphragmatic Hernia With Pulmonary Hypertension: Prolonged Use of Dexmedetomidine as a Pharmacologic Adjunct

Abstract: Introduction:Underdevelopment of the lung parenchyma associated with abnormal growth of pulmonary vasculature in neonates with congenital diaphragmatic hernia results in pulmonary hypertension which mandates smooth elective mechanical ventilation in postoperative period, for proper alveolar recruitment and oxygenation, allowing lungs to mature enough for its functional anatomy and physiology. Dexmedetomidine is sympatholytic, reduces pulmonary vascular resistance and exerts sedative and analgesic property to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Dexmedetomidine is an α-2 adrenergic agonist that has sedative and analgesic effects without suppressing respiratory drive. 28 29 30 A recent pediatric study found that using dexmedetomidine reduced the use of both benzodiazepines and opioids and was associated with less delirium, lower pain scores, and lower withdrawal scores. 28 When used in children on treatment for reactive pulmonary hypertension, dexmedetomidine led to an increase in systemic vascular resistance without affecting the pulmonary vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dexmedetomidine is an α-2 adrenergic agonist that has sedative and analgesic effects without suppressing respiratory drive. 28 29 30 A recent pediatric study found that using dexmedetomidine reduced the use of both benzodiazepines and opioids and was associated with less delirium, lower pain scores, and lower withdrawal scores. 28 When used in children on treatment for reactive pulmonary hypertension, dexmedetomidine led to an increase in systemic vascular resistance without affecting the pulmonary vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…31 A very small case series of prolonged perioperative dexmedetomidine in infants with CDH suggests the medication was tolerated well during the first 48 hours after hernia repair. 29 These early reports suggest it may provide adequate sedation without the known risks associated with benzodiazepines; however, much more research is needed to understand the safety and efficacy of dexmedetomidine in neonates, especially in the setting of prolonged use.…”
Section: Discussionmentioning
confidence: 99%